EFFICACY, TOLERABILITY AND SAFETY OF CANNABIS OIL IN CHILDREN WITH AUTISM: A LITERATURE REVIEW - Sousa Martins, Carolina; Moreira Lopes, Wander; Vieira Dias, Gustavo (Health and Society, 2025)
Autism Spectrum Disorder is a neurological condition that presents itself in diverse ways, mainly affecting communication and behavior. Given the heterogeneity and particularity of each case, the search for appropriate treatment still becomes a great challenge. In this scenario, the use of Cannabis sativa oil has been noted as a potential alternative treatment. This literature review study aims to assess the clinical experience with the use of full-spectrum Cannabis sativa oil, rich in cannabidiol, in the treatment of people diagnosed with autism spectrum disorder. The objective of the study was to investigate aspects of tolerability, safety and possible therapeutic effects, in addition to highlighting the importance of individualized strategies in the management of this population. This research is a narrative literature review with an integrative approach, with the objective of gathering, analyzing and synthesizing scientific evidence related to the therapeutic use of cannabinoids, especially cannabidiol and tetrahydrocannabinol, in patients diagnosed with Autism Spectrum Disorder. This literature review allowed us to consolidate relevant evidence about the therapeutic potential of cannabinoids, especially cannabidiol, as an adjuvant strategy in the management of the symptoms of Autism Spectrum Disorder. The studies analyzed indicate that the use of cannabidiol can contribute to the reduction of symptoms such as irritability, aggression, anxiety and sleep disorders, favoring the adaptive behavior and quality of life of patients with autism spectrum disorder and their caregivers.